Chemical and conformational studies of bacterial cell surface polysaccharide repeating units - Timol, Zaheer (Department of Chemistry, 2017)
Abstract Bacterial cell surface polysaccharides are primarily present as lipopolysaccharides or capsular polysaccharides. They are used by cells for both structure and function and have been shown to be a virulence factor of bacterial pathogens. Cell surface polysaccharides are widely utilised as antigenic components in vaccines and play an important role in the protection against numerous diseases including meningococcal disease and shigellosis. This study is composed of two parts: a computational section, which investigates the capsular polysaccharide (CPS) repeating unit (RU) conformations of meningococcal Y and W CPS vaccines and a second experimental component that involves synthetic studies toward the O-specific polysaccharide (O-SP) RU of Shigella sonnei. The CPS RU of MenY [→6)-α-D-Glc(1→4)-α-D-NeuNAc-(2→] and MenW [→6)-α-D-Gal(1→4)-α-D-NeuNAc-(2→] differ only in the orientation of the C-4 hydroxyl: equatorial in MenY and axial in MenW. However, groups Y and W CPS vaccines have different levels of antibody cross-protection. The purpose of the computational study was to determine if these observed differences may be attributed to CPS RU conformation. Potential of mean force calculations were applied to disaccharide RUs of MenY and MenW, and larger three repeating units (3RU) were simulated with molecular dynamics (MD) in solution. The molecular modelling showed that differences in RU conformation between the meningococcal groups arise primarily due to the structural differences between glucose and galactose; affecting the behaviour and orientation of the 2→6 dihedral linkage. The 2→6 linkages in the MenY 3RU adopt a single preferred orientation and consequently it has a single dominant molecular conformation. In contrast, the 2→6 linkages in the MenW 3RU move frequently between different rotameric conformations resulting in multiple conformational families. These results indicate significant conformational differences between the MenY and MenW CPS RUs, which may account for the different levels of cross-protection observed. The synthetic component was part of a larger study to develop a novel route towards the O-SP RU of S. sonnei for use in biological testing and physicochemical characterisation for vaccine development. The O-SP RU of S. sonnei is →4-α-L-AltNAc-(1→3)-β-D-FucNAc4N(1→. The multi-step synthesis was performed using known methodology as well as methods developed by the research group. The key 2,3-oxazolidinone protected intermediate was successfully synthesised in good yields and due to time constraints the final product synthesised was two steps away from the protected FucNAc4N residue. Additional studies were performed on the 2,3-oxazolidinone intermediate as part of a divergent synthesis strategy toward the AltNAcA residue of S. sonnei. Reactions were conducted whereby β and α derivatives of the 2,3-oxazolidinone intermediate were successfully synthesised in large scale and good yields for further studies to be performed by the group. i